2021
DOI: 10.3390/md19070378
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Approach for the Discovery of Environment-Related Pyran-2-Ones Chemodiversity in a Marine-Sourced Penicillium restrictum

Abstract: Very little is known about chemical interactions between fungi and their mollusc host within marine environments. Here, we investigated the metabolome of a Penicillium restrictum MMS417 strain isolated from the blue mussel Mytilus edulis collected on the Loire estuary, France. Following the OSMAC approach with the use of 14 culture media, the effect of salinity and of a mussel-derived medium on the metabolic expression were analysed using HPLC-UV/DAD-HRMS/MS. An untargeted metabolomics study was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 107 publications
1
7
0
Order By: Relevance
“…Host-derived media appear clearly more relevant than classical artificial culture media [21][22][23][24], as shown here by the presence of mussel FAs in the lipid composition of the fungus. We can assume that such lipids of hybrid origin are naturally produced within the bivalves, which could not have been observed otherwise.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Host-derived media appear clearly more relevant than classical artificial culture media [21][22][23][24], as shown here by the presence of mussel FAs in the lipid composition of the fungus. We can assume that such lipids of hybrid origin are naturally produced within the bivalves, which could not have been observed otherwise.…”
Section: Discussionmentioning
confidence: 76%
“…However, the most significantly altered part of the analysed metabolism was the FA composition of lipids. This result was unexpected as in a previous study focused on specialised metabolites it was shown that, when cultured in the MES-SSW medium, P. restricum MMS417 over-produced two classes of specialised metabolites, namely pyran-2-ones and lactam macrolides [21]. It therefore appears that the most important response was firstly the induction of lipid metabolism pathways necessary for the physiological adaptation of the fungus, before the expression of more complex biosynthetic mechanisms of specialised metabolism.…”
Section: Discussionmentioning
confidence: 89%
“…Normal and reverse phase chromatographic methods were applied to afford fractions from the AcOEt extract of fermentation of LXY140-3. Thirteen compounds, including one new organic acid 14, and 12 known compounds (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) were isolated and purified (Figure 5). The known compounds were determined as D-pantothenic acid methyl ester (15), [16] mevalonolactone ( 16), [17] 3,5-dihydroxydecanioc acid (17), [18] (À )-annularin C (18), [19] (1'R,2'S)-LLÀ P880γ (19), [20] PC-2 (20), [20] (6S,1'S)-LLÀ P880β (21), [21] 6S,1'S,2'R)-LLÀ P880β (22), [22] atlantinone B (23), [22] isochomophilone III (24), [23,24] isochomophilone VIII (25), [25] hypocrellone A (26), [26] respectively, by comparison of their MS, NMR, and specific rotation data with those of reported compounds (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…209 Soft coral-derived Penicillium strains yielded deoxyisoaustamide derivatives 554–560 , 210 and azaphilones 561 and 562 , 211 whilst deep-sea sediment-derived strains were the source of phenylhydrazone 563–565 , and enantiomeric quinazoline 566 and 567 derivatives, 212 benzamide 568 and 569 and leucine derivatives 570 and 571 , 213 penicyrone A analogues with an epoxy tetrahydrofuran ring 572 and 573 , 213 phenol furanone 574 , octanamide derivative 575 and decanoic acid derivatives 576 and 577 . 213 An untargeted metabolomics approach to examination of a P. restrictum extract led to isolation of pyran-2-one derivatives 578–582 , of which 579 was a known synthetic but new NP and 582 was a known terrestrial NP but a first time marine isolate 214 and P. sclerotiorum yielded azaphilones 583 and 584 . 215 Solitumergosterol A 585 , is an unique 6/6/6/6/5 steroid obtained from P. solitum from deep-sea sediment, 216 as were polyketide 586 and alkaloids 587 and 588 .…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%